Effect of Arthrocentesis in the Therapy of Temporomandibular Joint - I. Malachovský; D. Statelová (Czech Dental Chamber, 2008)
Arthrocentesis of temporomandibular joint is a procedure in which two syringe needles are inserted into intrarticular space to make a lavage removing adhesions. Through the same way also topical antibiotics, local anaesthetics and chondroprotective agents can be applied. Aim: To find out an effect and success this method in therapy of temporomandibular disorders. Methods: More over 419 from 1752 patients were treated by arthrocentesis. There were 348 women and 71 men. Results: In the group after arthrocentesis one year after therapy value of the pain was 2.5 and control group was 9. Motion of the mandible in the first group was 37mm and in second group was 27mm.Arthrocentesis is recommended as an alternative method replacing the more invasive treatment of acute and chronic morbid conditions of the structures of temporomandibular joint.